Efektivitas Pendekatan Kontekstual (Contextual Teaching And Learning) dalam Menulis Puisi - Hasnah P (Pepatudzu : Media Pendidikan dan Sosial Kemasyarakatan, 2020)
This study aims to describe the effectiveness of contextual learning in writing poetry in class X students of SMA Negeri 1 Wonomulyo Polewali Mandar. The design used in this study is an experimental design of the experimental-control posttest group design. Students who were sampled were 60 people divided into two groups, namely the first group as many as 30 people as an experimental group / class and the second group as many as 30 people as a control group/class. The results showed that the average value of student competence in writing poetry through the application of a contextual approach (experimental class) was 7,9 while the average value of students' ability to write poetry without the application of a contextual approach (control class) was 6,5. The results of the comparison of the coefficient of the average value of students (tcount) between the experimental class (X1) and the control class (X2) obtained by 4,51 is greater than the table at the 5% significance level and 95% confidence obtained ts 0, 95 =1,70. Because tcount is greater than ttable at the 5% significance level and 95% confidence, the null hypothesis (H0) is rejected and the hypothesis (H1) is accepted. So, the contextual approach is effectively applied in learning to write poetry for class X students of SMA Negeri 1 Wonomulyo.